Spenser, Ronsard, and DuBellay - Satterthwaite, Alfred W. (Book collections on Project MUSE., 1960)
Although it has been recognized that Edmund Spenser's poetry owes a debt to the work of the French poets of the Pleiade, particularly to Joachim du Bellay and Pierre de Ronsard, there has been no critical analysis of this relationship. Mr. Satterthwaite compares the work of the three poets, showing the relation between the English movement to write quantitative verse and the French experiments in vers mesures. He discusses the attitudes of the poets to their Muses and to contemporary literature, their ideas of time and mutability, their moral (or amoral) views of literature and of life their religious orientation, and their use of the Platonic and neo-Platonic theories that were a part of the inherited culture of the Renaissance.Originally published in 1960.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.